Bimetal phosphate / nitrogen-doped carbon hollow nanorod as well as preparation method and application thereof
By preparing bimetallic phosphate/nitrogen doped carbon hollow nanorod catalyst, the problem of slow reaction rate of zinc air batteries is solved, and the effect of improving reaction rate and reducing costs is achieved.
Patent Information
- Application Number
- CN202311555173.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-11-21
AI Technical Summary
During the charging and discharging process of existing zinc air batteries, the reaction rates of oxygen precipitation reaction and oxygen reduction reaction are relatively slow, which limits their large-scale application.
Bimetallic phosphate/nitrogen doped carbon hollow nanorods are used as catalysts. The preparation method includes forming a solid core-shell structure MIL-88-Fe nanomaterial, etching into a hollow structure, covering the polydopamine shell, and growing ZIF-L-Co on the outer layer, and finally pyrolyzed by high temperature.
The reaction rate of oxygen precipitation reaction and oxygen reduction reaction is improved, the specific surface area and active sites of the catalyst are increased, the cost is reduced, and the shape and electrocatalytic properties of the nanorod are maintained.
Smart Images

Figure CN119601681A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bimetallic phosphate / nitrogen-doped carbon hollow nanorods, and in particular to a bimetallic phosphate / nitrogen-doped carbon hollow nanorod and a preparation method and application thereof. Background Art
[0002] Due to the growing environmental problems and the explosive growth of global energy demand, the development of sustainable energy materials and green nanotechnology to build fuel cells, metal-air batteries and water electrolysis systems has attracted widespread attention. Zinc-air batteries (ZABs) have the advantages of high energy density, safety, reliability, low cost and environmental friendliness, and are considered to be important devices for achieving sustainable conversion of electrical energy and chemical energy. During the charge and discharge process of the battery, oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) occur on the electrodes, respectively. Both processes involve four-electron transfer and have the problem of slow reaction kinetics, which limits the large-scale application of rechargeable zinc-air batteries.
[0003] The most effective way to solve the above problems is to develop bifunctional catalysts to simultaneously increase the reaction rates of OER and ORR. Generally, the precious metal Pt is considered to be the best ORR catalyst, while Ru, Ir and their corresponding oxides RuO2 and IrO2 are considered to be efficient OER catalysts. However, precious metals have low natural abundance, high prices, poor durability, and existing precious metals cannot promote OER and ORR reactions at the same time. Therefore, exploring low-cost, bifunctional catalysts is crucial to promoting the development of reversible zinc-air batteries. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods. The catalyst prepared by the method has a typical hollow nanorod structure, which has a higher specific surface area, more active sites, low price and can simultaneously improve the reaction rates of OER and ORR.
[0005] To achieve the above object, the present invention adopts the following technical solution: a method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods, comprising the following steps:
[0006] S1. dissolving fumaric acid in deionized water and stirring thoroughly at 40-100° C. to form solution 1;
[0007] Dissolve a water-soluble iron salt in deionized water and stir to form solution 2;
[0008] The solution 1 and the solution 2 were mixed and stirred, and then transferred to a polytetrafluoroethylene-lined autoclave, and kept at 80-140°C for 3-9 hours, and then the product was collected by centrifugation, washed with ethanol and dried to obtain iron-based MIL-88-Fe solid nanorods;
[0009] S2, dispersing the iron-based MIL-88-Fe solid nanorods prepared in step S1 in deionized water, stirring evenly to form solution 3, and preparing a phytic acid solution at the same time;
[0010] The solution 3 was mixed with the phytic acid solution, and then placed in an oil bath at 60-120°C for 2-5 hours, the product was collected by centrifugation, washed with ethanol and dried to obtain iron-based MIL-88-Fe hollow nanorods;
[0011] S3, dissolving the iron-based MIL-88-Fe hollow nanorods prepared in step S2 in Tris buffer, and then adding dopamine hydrochloride to form solution 4;
[0012] The solution 4 was stirred to react fully, and then the product was collected by centrifugation, washed with ethanol and dried to obtain the iron-based hollow nanorods MIL-88-Fe wrapped with polydopamine PDA, which were recorded as MIL-88-Fe@PDA hollow nanorods;
[0013] S4, dispersing the MIL-88-Fe@PDA hollow nanorods and PVP prepared in step S3 into ethanol, and stirring thoroughly to form solution 5;
[0014] Dissolve 2-methylimidazole in deionized water to form solution 6;
[0015] Dissolving cobalt nitrate hexahydrate in deionized water to form solution 7;
[0016] Then, solution 5, solution 6, and solution 7 were fully mixed and stirred, and then the precipitate was collected by centrifugation, washed with ethanol, and dried to obtain iron-based hollow nanorods wrapped by polydopamine, and cobalt-based nanoparticles were epitaxially grown on the surface of polydopamine, which was recorded as MIL-88-Fe@PDA@Co-ZIF-L hollow nanorods;
[0017] S5. Place the MIL-88-Fe@PDA@ZIF-L-Co hollow nanorods prepared in step S4 into a porcelain boat, then place the porcelain boat in a tubular furnace, heat to 200-400°C in a nitrogen atmosphere and keep warm for 0.5-2h, then heat to 600-800°C and keep warm for 1-6h, and cool to room temperature to obtain bimetallic phosphate / nitrogen-doped carbon hollow nanorods.
[0018] As a further improvement of the preparation method of bimetallic phosphate / nitrogen-doped carbon hollow nanorods:
[0019] Preferably, the water-soluble iron salt is one of ferric nitrate nonahydrate, ferric acetate tetrahydrate, and ferric chloride hexahydrate.
[0020] Preferably, the concentration of fumaric acid in solution 1 is 0.603-6.03 mol / L, the concentration of water-soluble iron salt in solution 2 is 0.026 mol / L-0.26 mol / L, the molar concentration ratio of fumaric acid in solution 1 to the water-soluble iron salt in solution 2 is 6.03:0.26, and solution 1 and solution 2 are mixed in a volume ratio of 4:1.
[0021] Preferably, in step S2, the concentrations of solution 3 and the phytic acid solution are the same and are both 0.01-0.1 g / mL, and solution 3 and the phytic acid solution are mixed in equal volumes.
[0022] Preferably, the concentration of the iron-based MIL-88-Fe hollow nanorods in the solution 4 of step S3 is 0.00125-0.0125 g / mL, and the concentration ratio of the iron-based MIL-88-Fe hollow nanorods to dopamine hydrochloride is 2:1.
[0023] Preferably, the dispersion concentrations of MIL-88-Fe@PDA and PVP in solution 5 of step S4 are the same and are both 0.0008-0.008 g / mL; the concentration of 2-methylimidazole in solution 6 is 0.00308-0.0328 g / mL; and the concentration of cobalt nitrate hexahydrate in solution 7 is 0.00145-0.0145 g / mL.
[0024] Preferably, the concentration ratio of PVP in solution 5, the concentration of 2-methylimidazole in solution 6 and the concentration ratio of cobalt nitrate hexahydrate in solution 7 is 8:30.8:14.5, and solution 5, solution 6 and solution 7 are mixed in a volume ratio of 8:8:5.
[0025] Preferably, the heating rate of the tube furnace in step S5 is 1-10° C. / min.
[0026] The second object of the present invention is to provide a bimetallic phosphate / nitrogen-doped carbon hollow nanorod prepared by any one of the above preparation methods.
[0027] The third object of the present invention is to provide an application of the above-mentioned bimetallic phosphate / nitrogen-doped carbon hollow nanorods in zinc-air batteries.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1) The method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods of the present invention is as follows: first, a MIL-88-Fe nanomaterial with a solid core-shell structure is prepared, and then the solid MIL-88-Fe nanomaterial is etched into a hollow structure by using phytic acid etching technology, and then the coating ability of polydopamine is further utilized to coat a layer of polydopamine shell on the outer surface of the MIL-88-Fe hollow nanorods to form a MIL-88-Fe@PDA core-shell structure, and then a layer of ZIF-L-Co is coated on the outer layer to form MIL-88-Fe@PDA@ZIF-L-Co, and finally after high-temperature pyrolysis, the morphology thereof does not change significantly, and the shape of the hollow carbon nanorods is well maintained.
[0030] 2) Hollow structure materials have a high specific surface area, which can achieve rapid mass transfer and provide more active sites, thereby accelerating surface / interface reactions. Their unique structure optimizes the effective specific surface area and the charge and mass transfer during the electrocatalytic process, providing a promising platform for the preparation of new electrocatalysts.
[0031] 3) Compared with the traditional solid rod structure, the bimetallic phosphate / nitrogen-doped carbon hollow nanorod structure prepared by the present invention has a higher specific surface area, so it can accommodate more active sites, and the thin shell will not hinder the mass transfer process in the electrocatalytic process; the main skeleton of the catalyst is nitrogen-doped carbon, which has good conductivity, so it can accelerate the charge transfer process of the electrocatalytic reaction.
[0032] 4) Precious metals are expensive and have low natural reserves. In the bimetallic phosphate / nitrogen-doped carbon hollow nanorods prepared by the present invention, iron and cobalt are transition metals and are inexpensive. The bimetallic phosphate / nitrogen-doped carbon hollow nanorods are used as catalysts to catalyze oxygen reduction reactions and drive oxygen evolution reactions, thereby meeting the needs of rechargeable zinc-air batteries.
[0033] 5) The bimetallic phosphate / nitrogen-doped carbon hollow nanorod catalyst prepared by the present invention has very good performance, both the oxygen reduction catalyst (Pt / C) and the oxygen evolution catalyst (RuO2) are good, showing potential application prospects to replace commercial precious metal catalysts, and the assembled zinc-air battery can be repeatedly charged and discharged for a long period of time. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A flow chart of the synthesis of bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalysts according to the present invention;
[0035] Figure 2 is the X-ray powder diffraction pattern of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0036] Figure 3is the Fe signal in the X-ray photoelectron spectrum of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0037] Figure 4 is the Co signal in the X-ray photoelectron spectrum of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0038] Figure 5 is the C signal in the X-ray photoelectron spectrum of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0039] Figure 6 is the N signal in the X-ray photoelectron spectrum of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0040] Figure 7 is the O signal in the X-ray photoelectron spectrum of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0041] Figure 8 is the P signal in the X-ray photoelectron spectrum of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0042] Fig. 9 This is a Raman spectrum of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0043] Fig.10 is a transmission electron microscopy image of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0044] Fig.11 This is a high-resolution transmission electron microscopy image of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1;
[0045] Fig.12 The oxygen evolution reaction curve of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1 and the oxygen evolution reaction curve of the noble metal RuO2; (solid line - our synthesized catalyst; dotted line - commercial RuO2 catalyst)
[0046] Fig.13 The oxygen reduction reaction curve of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst prepared in Example 1 and the oxygen reduction reaction curve of the noble metal Pt / C; (solid line - our synthesized catalyst; dashed line - commercial Pt / C catalyst)
[0047] Fig.14The charge-discharge polarization curves of the bimetallic phosphate / nitrogen-doped carbon hollow nanorods prepared in Example 1 as an electrocatalyst, and the charge-discharge polarization curves of the RuO2 and Pt / C mixed catalyst; (solid line - the catalyst synthesized by us; dotted line - commercial RuO2 and Pt / C mixed catalyst).
[0048] Fig.15 The charge and discharge curves of the bimetallic phosphate / nitrogen-doped carbon hollow nanorods prepared in Example 1 as an electrocatalyst, as well as the charge and discharge curves of the RuO2 and Pt / C mixed catalyst; (solid line - the catalyst synthesized by us; dotted line - commercial RuO2 and Pt / C mixed catalyst). DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0050] Example 1
[0051] This embodiment provides a method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods, comprising the following steps:
[0052] Preparation of S1.MIL-88-Fe solid nanorods
[0053] Dissolve fumaric acid in deionized water to a concentration of 6.03 mol / L, and stir in an oil bath at 70°C for 10 min to form solution 1;
[0054] Dissolve ferric nitrate nonahydrate in deionized water to a concentration of 0.26 mol / L, and stir to form solution 2;
[0055] Solution 1 and solution 2 were mixed in a volume ratio of 4:1, stirred for 10 min, and then transferred to a polytetrafluoroethylene-lined autoclave, kept at 110 °C for 6 h, and then the product was collected by centrifugation, washed with ethanol, and dried to obtain MIL-88-Fe solid nanorods;
[0056] Preparation of S2.MIL-88-Fe hollow nanorods
[0057] The MIL-88-Fe solid nanorods prepared in step S1 were dispersed in deionized water at a dispersion concentration of 0.01 g / mL, and stirred to form solution 3; a 0.1 mol / L phytic acid solution was prepared, mixed with solution 3 at a volume ratio of 1:1, and then placed in an oil bath at 90°C for 3 h, the product was collected by centrifugation, washed with ethanol and dried to obtain MIL-88-Fe hollow nanorods;
[0058] S3. Synthesis of polydopamine-coated MIL-88-Fe hollow nanorods, MIL-88-Fe@PDA
[0059] The MIL-88-Fe hollow nanorods prepared in step S2 were dissolved in Tris buffer at a concentration of 0.00125 g / mL, and dopamine hydrochloride was added at a concentration of 0.000625 g / mL to form solution 4; solution 4 was stirred for 24 h, the product was collected by centrifugation, and the product was washed with ethanol and dried to obtain MIL-88-Fe@PDA hollow nanorods;
[0060] S4. Synthesis of MIL-88-Fe@PDA@ZIF-L-Co hollow nanorods
[0061] The MIL-88-Fe@PDA hollow nanorods and polyvinyl pyrrolidone (PVP) prepared in step S3 were dispersed in ethanol, wherein the dispersion concentration of MIL-88-Fe@PDA was 0.0008 g / mL, and the dispersion concentration of polyvinyl pyrrolidone (PVP) was 0.0008 g / mL, and stirred for 2 h to form solution 5;
[0062] Dissolve 2-methylimidazole in deionized water at a concentration of 0.00308 g / mL to form solution 6;
[0063] Dissolving cobalt nitrate hexahydrate in deionized water at a concentration of 0.00145 g / mL to form solution 7;
[0064] Then, solutions 5, 6, and 7 were fully mixed at a volume ratio of 8:8:5, stirred for 3 h, and then the precipitate was collected by centrifugation, washed with ethanol, and dried to obtain MIL-88-Fe@PDA@ZIF-L-Co hollow nanorods;
[0065] S5. Synthesis of bimetallic phosphate / nitrogen-doped carbon hollow nanorods
[0066] The MIL-88-Fe@PDA@ZIF-L-Co hollow nanorods prepared in step S4 were placed in a porcelain boat, and then the porcelain boat was placed in a tubular furnace. Under a nitrogen atmosphere, the temperature was increased to 300°C at a heating rate of 3°C / min and kept for 1 hour, then the temperature was increased to 700°C and kept for 2 hours, and then cooled to room temperature to obtain bimetallic phosphate / nitrogen-doped carbon hollow nanorods.
[0067] Figure 1The flowchart of the synthesized bimetallic phosphate / nitrogen-doped carbon hollow nanorods is shown. The preparation method includes the following steps: first, prepare MIL-88-Fe solid nanorods, then use phytic acid etching technology to etch the above solid nanorods into hollow structures, then coat the outer surface of the hollow structure with a layer of polydopamine shell to form a MIL-88-Fe@PDA core-shell structure, and then grow ZIF-L-Co on its surface, and then pyrolyze it at high temperature to maintain the morphology well, that is, a catalyst with a hollow nanorod structure is formed; from the perspective of material evolution, both the fumaric acid and polydopamine in the MIL-88-Fe structure are converted into a carbon matrix, and then we use phytic acid as a P source, and the Fe in the MIL-88-Fe structure and the Co in the ZIF-L-Co react with P to generate Fe and Co phosphates, which are respectively located in the inner and outer layers of the hollow nanorods with polydopamine as the intermediate layer. Under the synergistic effect of Fe and Co phosphates, the mass transfer and charge transfer of the catalyst are accelerated, greatly enhancing its electrocatalytic performance.
[0068] Figure 2 The X-ray powder diffraction pattern of the synthesized bimetallic phosphate / nitrogen-doped carbon hollow nanorods and the corresponding standard card. The standard card numbers are ICDD 00-034-1378 and ICDD 00-078-2285, proving that the synthesized electrocatalyst contains cobalt and iron phosphates.
[0069] Figure 3 The Fe signal in the X-ray photoelectron spectrum of the synthesized bimetallic phosphate / nitrogen-doped carbon hollow nanorods; the peaks at 710.1eV and 722.8eV correspond to Fe-N bonds, 711.6eV and 724.7eV correspond to Fe-O bonds, 713.7eV and 726.3eV correspond to trivalent Fe, and 716.8eV and 729.6eV correspond to satellite peaks, proving the presence of Fe components in the catalyst.
[0070] Figure 4 The Co signal in the X-ray photoelectron spectrum of the synthesized bimetallic phosphate / nitrogen-doped carbon hollow nanorods; the peaks at 780.7 eV and 796.2 eV correspond to Co-N bonds, 782.0 eV and 798.2 eV correspond to divalent Co, and 785.6 eV and 802.7 eV correspond to satellite peaks, proving the presence of Co components in the catalyst.
[0071] Figure 5 It is the C signal in the X-ray photoelectron spectrum of the synthesized bimetallic phosphate / nitrogen-doped carbon hollow nanorods; the four peaks located at 284.3, 285.1, 285.8 and 288.8 eV correspond to CC, CP, CN and C=O components, respectively, proving the presence of C component in the catalyst.
[0072] Figure 6 It is the N signal in the X-ray photoelectron spectrum of the synthesized bimetallic phosphate / nitrogen-doped carbon hollow nanorods; the four peaks located at 398.1, 399.3, 400.4 and 401.2 eV correspond to pyridine-N, MN structure, pyrrole-N and graphite-N, respectively, proving the presence of N component in the catalyst.
[0073] Figure 7 This is the O signal in the X-ray photoelectron spectrum of the synthesized bimetallic phosphate / nitrogen-doped carbon hollow nanorods; the OP bond is located at 531.4 eV, and the OC bond is located at 533.1 eV, proving the presence of O components in the catalyst.
[0074] Figure 8 It is the P signal in the X-ray photoelectron spectrum of the synthesized bimetallic phosphate / nitrogen-doped carbon hollow nanorods; the one at 133.8 eV is the PC bond, and the one at 134.7 eV is the PO bond, proving the presence of a P component in the catalyst.
[0075] Fig. 9 Raman spectra of bimetallic phosphate / nitrogen-doped carbon hollow nanorods; Fig. 9 It can be clearly seen that at 1350cm -1 and 1580cm -1 There are two obvious peaks at the center, corresponding to the D band and G band of carbon materials. D / I G ) is an important parameter to characterize the graphitization degree of carbon materials. The smaller the ratio, the higher the graphitization degree of the carbon material. According to calculations, the I D / I G It is about 0.95, which not only shows that the catalyst contains carbon material, but also has a high degree of graphitization.
[0076] Fig.10 This is a transmission electron microscope photo of bimetallic phosphate / nitrogen-doped carbon hollow nanorods. From the picture, it can be seen that the morphology of the sample is a rod-like structure, and a careful observation shows that the nanorods maintain a good hollow structure.
[0077] Fig.11 This is a high-resolution transmission electron microscopy image of bimetallic phosphate / nitrogen-doped carbon hollow nanorods. Fig.11 The lattice spacings of Co2P2O7 and Fe(PO3)2 are shown at 0.351nm and 0.186nm, corresponding to the (121) crystal plane of the Co2P2O7 component and the (133) crystal plane of the Fe(PO3)2 component, respectively.
[0078] Fig.12The oxygen evolution reaction curves of bimetallic phosphate / nitrogen-doped carbon hollow nanorods and the oxygen evolution reaction curves of noble metal RuO2 are shown in Figure 2. According to calculations, when bimetallic phosphate / nitrogen-doped carbon hollow nanorods are used as catalysts, the current density reaches 10 mA / cm 2 The overpotential required for the reaction is 291 mV, which is higher than the overpotential of the noble metal RuO2 of 302 mV, showing a certain superiority. This shows that the hollow structure increases the specific surface area, promotes charge transfer, optimizes the adsorption and desorption energy barriers of reaction intermediates, and ultimately improves the electrocatalytic activity.
[0079] Fig.13 The oxygen reduction reaction curves of bimetallic phosphate / nitrogen-doped carbon hollow nanorods and the oxygen reduction reaction curves of noble metal Pt / C. According to calculations, when bimetallic phosphate / nitrogen-doped carbon hollow nanorods are used as catalysts, the half-wave potential is 0.912V and the limiting current is 6.32mA / cm 2 ; Better performance than precious metal Pt / C (0.835V, 5.31mA / cm 2 ).
[0080] Fig.14 The charge and discharge polarization curves of bimetallic phosphate / nitrogen-doped carbon hollow nanorods as electrocatalysts. 50mA / cm 2 Under the current density, the △E of bimetallic phosphate / nitrogen-doped carbon hollow nanorods is 1.0V, and that of RuO2 and Pt / C mixed catalyst is 1.360V, showing certain superiority.
[0081] Fig.15 The charge and discharge curves of bimetallic phosphate / nitrogen-doped carbon hollow nanorods as electrocatalysts. As can be seen from the figure, the battery's charge and discharge time is more than 147 hours, △E is 0.14V at 3 hours, △E is 0.35V at 70 hours, and △E is 0.64V at 147 hours, which is much better than RuO2 and Pt / C mixed catalysts.
[0082] Example 2
[0083] This embodiment provides a method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods. The specific preparation steps refer to Example 1, except that ferric acetate tetrahydrate is used in solution 2 of step S1, and bimetallic phosphate / nitrogen-doped carbon hollow nanorods are finally prepared.
[0084] The bimetallic phosphate / nitrogen-doped carbon hollow nanorods prepared in this example were used as catalysts. The current density was 10 mA / cm 2 The overpotential of the oxygen evolution reaction is 310mV, showing excellent electrocatalytic oxygen evolution activity. For the oxygen reduction reaction, the half-wave potential is 0.893V and the limiting current is 5.78mA / cm2 When the catalyst is used as the air electrode, the assembled rechargeable zinc-air battery has a current density of 50 mA / cm 2 The △E=0.85V at 2h and the charge and discharge time of the battery can reach 135 hours, and the △E=0.276V at 2h and the △E=0.353V at 79h, which are better than the precious metal Pt / C+RuO2.
[0085] Example 3
[0086] This embodiment provides a method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods. The specific preparation steps refer to Example 1, except that ferric chloride hexahydrate is used in solution 2 of step S1, and bimetallic phosphate / nitrogen-doped carbon hollow nanorods are finally prepared.
[0087] The bimetallic phosphate / nitrogen-doped carbon hollow nanorods prepared in this example were used as catalysts. The current density reached 10 mA / cm 2 The overpotential required is 312mV; the half-wave potential is 0.889V, and the limiting current is 5.64mA / cm 2 ; Charge and discharge polarization curves of bimetallic phosphate / nitrogen-doped carbon hollow nanorod catalyst as electrocatalyst. 50mA / cm 2 Under the current density, the △E of bimetallic phosphate / nitrogen-doped carbon hollow nanorods is 1.34V; the charge and discharge curve as an electrocatalyst. The battery charge and discharge time is more than 130h, the △E is 0.25V at 2h; △E is 0.32V at 60h; △E is 0.65V at 130h.
[0088] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods, characterized in that: The steps include: S1. dissolving fumaric acid in deionized water and stirring thoroughly at 40-100° C. to form solution 1; Dissolve a water-soluble iron salt in deionized water and stir to form solution 2; The solution 1 and the solution 2 were mixed and stirred, and then transferred to a polytetrafluoroethylene-lined autoclave, and kept at 80-140°C for 3-9 hours, and then the product was collected by centrifugation, washed with ethanol and dried to obtain iron-based MIL-88-Fe solid nanorods; S2, dispersing the iron-based MIL-88-Fe solid nanorods prepared in step S1 in deionized water, stirring evenly to form solution 3, and preparing a phytic acid solution at the same time; The solution 3 was mixed with the phytic acid solution, and then placed in an oil bath at 60-120°C for 2-5 hours, the product was collected by centrifugation, washed with ethanol and dried to obtain iron-based MIL-88-Fe hollow nanorods; S3, dissolving the iron-based MIL-88-Fe hollow nanorods prepared in step S2 in Tris buffer, and then adding dopamine hydrochloride to form solution 4; The solution 4 was stirred to react fully, and then the product was collected by centrifugation, washed with ethanol and dried to obtain the iron-based hollow nanorods MIL-88-Fe wrapped with polydopamine PDA, which were recorded as MIL-88-Fe@PDA hollow nanorods; S4, dispersing the MIL-88-Fe@PDA hollow nanorods and PVP prepared in step S3 into ethanol, and stirring thoroughly to form solution 5; Dissolve 2-methylimidazole in deionized water to form solution 6; Dissolving cobalt nitrate hexahydrate in deionized water to form solution 7; Then, solution 5, solution 6, and solution 7 were fully mixed and stirred, and then the precipitate was collected by centrifugation, washed with ethanol, and dried to obtain iron-based hollow nanorods wrapped by polydopamine, and cobalt-based nanoparticles were epitaxially grown on the surface of polydopamine, which was recorded as MIL-88-Fe@PDA@Co-ZIF-L hollow nanorods; S5. Place the MIL-88-Fe@PDA@ZIF-L-Co hollow nanorods prepared in step S4 into a porcelain boat, then place the porcelain boat in a tubular furnace, heat to 200-400°C in a nitrogen atmosphere and keep warm for 0.5-2h, then heat to 600-800°C and keep warm for 1-6h, and cool to room temperature to obtain bimetallic phosphate / nitrogen-doped carbon hollow nanorods.
2. The method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods according to claim 1, characterized in that: The water-soluble iron salt is one of ferric nitrate nonahydrate, ferric acetate tetrahydrate and ferric chloride hexahydrate.
3. The method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods according to claim 1 or 2, characterized in that: The concentration of fumaric acid in solution 1 is 0.603-6.03 mol / L, the concentration of water-soluble iron salt in solution 2 is 0.026 mol / L-0.26 mol / L, the molar concentration ratio of fumaric acid in solution 1 to the water-soluble iron salt in solution 2 is 6.03:0.26, and solution 1 and solution 2 are mixed in a volume ratio of 4:
1.
4. The method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods according to claim 1, characterized in that: In step S2, the concentrations of solution 3 and the phytic acid solution are the same and are both 0.01-0.1 g / mL, and solution 3 and the phytic acid solution are mixed in equal volumes.
5. The method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods according to claim 1, characterized in that: The concentration of the iron-based MIL-88-Fe hollow nanorods in the solution 4 of step S3 is 0.00125-0.0125 g / mL, and the concentration ratio of the iron-based MIL-88-Fe hollow nanorods to dopamine hydrochloride is 2:
1.
6. The method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods according to claim 1, characterized in that: The dispersion concentrations of MIL-88-Fe@PDA and PVP in solution 5 of step S4 are the same and are both 0.0008-0.008 g / mL; the concentration of 2-methylimidazole in solution 6 is 0.00308-0.0328 g / mL; and the concentration of cobalt nitrate hexahydrate in solution 7 is 0.00145-0.0145 g / mL.
7. The method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods according to claim 6, characterized in that: The concentration ratio of PVP in solution 5, the concentration of 2-methylimidazole in solution 6 and the concentration ratio of cobalt nitrate hexahydrate in solution 7 is 8:30.8:14.5, and solution 5, solution 6 and solution 7 are mixed in a volume ratio of 8:8:
5.
8. The method for preparing bimetallic phosphate / nitrogen-doped carbon hollow nanorods according to claim 1, characterized in that: The heating rate of the tube furnace in step S5 is 1-10°C / min.
9. A bimetallic phosphate / nitrogen-doped carbon hollow nanorod prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the bimetallic phosphate / nitrogen-doped carbon hollow nanorod electrocatalyst according to claim 9 in a zinc-air battery.
Citation Information
Patent Citations
Preparation method of metal-organic framework fiber membrane
CN107159130A
Preparation method and application of transition metal-based double-shell carbon nanobox
CN115149011A
Synthetic method of open type hollow FeCoNiP-coated CQDs nanotube structure for electrolyzing seawater
CN115323428A
Preparation method of composite difunctional electrocatalyst and application of composite difunctional electrocatalyst in high-power zinc-air battery
CN115458753A
Soldering inspection equipment and soldering inspection method using the same
KR102150281B1